(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article outlines the cognitive process of school-age children with mental disabilities, perception characteristics, ways to verify perception, didactic tools and methodological approaches to developing perception, and technologies for developing the perception of children with disabilities before school.